Student Engagement in the Lithuanian EFL Classroom - Daukšaitė-Kolpakovienė, Aurelija (Studies in Teaching and Education, 2025)
This article presents the results of a qualitative and quantitative study that utilised an online questionnaire to research Lithuanian university EFL students’ self-perceived engagement. It assesses the role of engagement in the EFL classroom through the following research questions: 1) what engages students studying English as a foreign language? 2) what disengages students studying English as a foreign language? 3) how do students describe their own engagement while learning English as a foreign language? The findings suggest that the students are engaged by classroom activities (mostly speaking), long-term personal goals, classroom atmosphere, their own mood, and other factors that may differ from student to student. Disengagement is mostly caused by early lecture time, students themselves, other students, reading tasks, and homework tasks. The students also reflected on their own engagement while studying English, which helped to see the bigger picture regarding their (dis)engagement, as particular challenges, experienced outside the classroom, could also contribute significantly.
Keywords: disengagement; EFL; engagement; Lithuanian university students